Cultural conduits: music, media, and migrant identity in South Africa - Nyamnjoh, Sue (Centre for Film and Media Studies, 2025)
This study aims to explore the complexities of how the African migrant identity in South Africa is mediated, with a particular focus on the role of newspapers and music as mediums for shaping public perceptions. By examining how African migrants are depicted in South African newspapers, the research seeks to uncover dominant narratives, themes, and discourses that frame these portrayals. Additionally, the study delves into the potential of music as an alternative space for inclusion, investigating how musical expressions mediate migration-related themes and foster a sense of belonging. The main argument of the study is that while traditional media often perpetuates negative stereotypes and exclusionary narratives, music offers a unique platform for migrants to articulate their experiences and challenge prevailing ideologies. This dichotomy underscores the need for a more balanced and contextually informed media coverage that recognizes the complexities of migration and promotes social cohesion and understanding. Methodologically, the study employs a rigorous discourse analysis (DA) and critical discourse analysis (CDA) framework to dissect the language, symbols, and practices through which media and music construct migration narratives. The research involves a detailed examination of news articles from prominent South African newspapers and a critical analysis of selected music lyrics and videos that address migration themes. The findings reveal that media narratives in newspapers often frame migrants as threats or burdens, which exacerbates societal fears and prejudices. In contrast, music serves as a powerful conduit for expressing migrant identities and experiences, highlighting shared struggles and fostering empathy. Furthermore, music can serve as an alternative site of inclusion, particularly if we broaden our ideas of citizenship to ones that are more flexible and accommodating of diverse identities and experiences. This study concludes that to achieve a more inclusive society, it is crucial for media practitioners, policymakers, and cultural actors to develop narratives that accurately reflect the multifaceted nature of migration and actively promote the integration of African migrants in South Africa. By integrating insights from media and music, this research contributes to a deeper understanding of the socio-cultural dynamics at play in the representation of migrants. It offers valuable perspectives for enhancing media practices and fostering a more inclusive public dialogue on migration.